THE ROLE OF ART TECHNOLOGIES IN THE METHODICAL REGULATION OF THE VOCATIONAL EDUCATION PROCESS - Sayfullayeva I. Q. (Web of Journals Publishing, 2023)
This article discusses the role of art technologies in the methodological systematization of the professional activities of future speech therapists.
Keywords: art technology, speech acceleration, game activity, professional activity, disabled child, isotherapy, doll therapy, music therapy, sand therapy, play therapy.